2021
DOI: 10.1007/s13762-021-03739-8
|View full text |Cite
|
Sign up to set email alerts
|

An environmental and economic evaluation of solar photovoltaic thermal dryer

Abstract: The up-gradation of the conventional indirect mode forced convection solar dryer to Photovoltaic thermal (PVT) based solar dryer is advantageous in terms of energysaving ability, efficiency, self-sufficient design, and ability to work without any additional electrical energy requirement. However, there is a requirement for a comprehensive analysis of the energy, exergy, and environ-economic parameters for developing an efficient and sustainable PVT solar dryer. In this study, a PVT based indirect mode solar dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Solar radiation can be turned into thermal energy (heat) or electrical energy, with the former being more straightforward [7], as the heat emitted from the sun is used directly for heating purposes for a long time. However, solar heat (thermal energy) can be used in so many different applications and ways in our current time, as the technology for solar collectors and dryers has improved drastically, as can be seen from the literature [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Solar radiation can be turned into thermal energy (heat) or electrical energy, with the former being more straightforward [7], as the heat emitted from the sun is used directly for heating purposes for a long time. However, solar heat (thermal energy) can be used in so many different applications and ways in our current time, as the technology for solar collectors and dryers has improved drastically, as can be seen from the literature [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This is important to prevent postharvest losses of agricultural produce owing to primitive methods of post-harvest handling and storage. The drying of agricultural products happens to be the first unit operation in the preservation and storage of most agricultural products to enhance their shelf-life [3]. Drying removes the moisture from the product to a stable level where microbes that cause deterioration might not thrive.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the matrix inversion technique was used to determine the temperature for each component of SPDFPVTC with NUCSR. Equations ( 4), ( 5), ( 9), ( 13), ( 14), ( 17), (20), and ( 24) can be rearranged in 8 × 8 matrix form (½A½T = ½B) as follows:…”
Section: Startmentioning
confidence: 99%
“…Al-Damook et al [19] optimized SPDFPVTC using CFD analysis and found that the electrical and thermal efficiencies were 50.1% and 10.5%, respectively, with optimized parameters. Gupta et al [20] developed a solar dryer using the PVTC having a wavy-shaped absorber plate. This study presented the daily performance of the proposed PVTC and reported that the electrical and thermal efficiencies varied from 12.28 to 14.27% and 23.89% to 62.37%, respectively.…”
Section: Introductionmentioning
confidence: 99%